2017
DOI: 10.1016/j.devcel.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Cell Contact Area Affects Notch Signaling and Notch-Dependent Patterning

Abstract: SummaryDuring development, cells undergo dramatic changes in their morphology. By affecting contact geometry, these morphological changes could influence cellular communication. However, it has remained unclear whether and how signaling depends on contact geometry. This question is particularly relevant for Notch signaling, which coordinates neighboring cell fates through direct cell-cell signaling. Using micropatterning with a receptor trans-endocytosis assay, we show that signaling between pairs of cells cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
171
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(189 citation statements)
references
References 36 publications
8
171
0
Order By: Relevance
“…Interestingly, we noted smaller cells to be more likely to differentiate, which is consistent with previous experimental observations showing that Notch signalling is dependent on cell-cell contact area and that hair-cell precursors in the inner ear tend to be smaller (Shaya et al, 2017). We further evaluated the effect of the growth rate and observed that in fast-growing tissues, Notch activity becomes more homogeneous and fewer cells have low Notch activity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, we noted smaller cells to be more likely to differentiate, which is consistent with previous experimental observations showing that Notch signalling is dependent on cell-cell contact area and that hair-cell precursors in the inner ear tend to be smaller (Shaya et al, 2017). We further evaluated the effect of the growth rate and observed that in fast-growing tissues, Notch activity becomes more homogeneous and fewer cells have low Notch activity.…”
Section: Discussionsupporting
confidence: 90%
“…We also observed that cells with low Notch signal, and consequently high levels of Delta, tend to be smaller (Figure 1a,c). This is consistent with experimental observations showing that the cell contact area affects Notch signalling and that smaller cells are more likely to differentiate, as observed in hair cell precursors in the inner ear (Shaya et al, 2017).…”
Section: Effect Of Asymmetry In Cell Division On Notch-mediated Cell supporting
confidence: 92%
See 1 more Smart Citation
“…Thus, cochlear cell fate commitment is extremely sensitive to the levels of Notch signaling. In this way, Fringe proteins can influence hair cell specification …”
Section: Grns Related To Notch Signalingmentioning
confidence: 99%
“…The exchange of Jagged ligands that bind through the Notch receptor facilitates bi-directional cross-talk between cells, stabilizes hybrid E/M cell phenotype(s) and promotes resistance to therapies (55)(56)(57). Previous efforts to couple EMT with intercellular signaling have disregarded the loss of cell-cell adhesion leading to a reduced cell-to-cell signaling between mesenchymal cells (58). Also, we recently showed that JAG1, a Jagged ligand subtype, promotes the growth of tumor organoids in breast cancer cells in vitro (12).…”
Section: What Molecular Mechanisms Can Maximize the Metastatic Potentmentioning
confidence: 99%